Karyotype analysis of Eleutherine bulbosa (Iridaceae) from Kalimantan, Indonesia - Noor Aini Habibah; Woro Anindito Sri Tunjung; Meti Indrowati; Alin Liana (Society for Indonesian Biodiversity, 2025)
Abstract. Habibah NA, Tunjung WAS, Indrowati M, Liana A. 2025. Karyotype analysis of Eleutherine bulbosa (Iridaceae) from Kalimantan, Indonesia. Biodiversitas 26: 2486-2494. Eleutherine bulbosa or Dayak onion belongs to the family Iridaceae and is widely distributed in Indonesia. However, research on E. bulbosa, especially for the cytogenetic aspect is poorly reported. This study aimed to analyze karyotype of E. bulbosa chromosomes collected from Kalimantan, Indonesia. Chromosome observation was carried out using a modified squash method. The results showed that E. bulbosa has basic chromosome number of 2n: 12. Although it has the same number of chromosomes, each sample shows a different chromosome formula. Those from East Kalimantan and Central Kalimantan have a chromosome formula of 2n=2x=12m. Meanwhile, samples from South Kalimantan have a chromosome formula of 2n=2x=10m+2sm. In comparison, those from North Kalimantan and West Kalimantan have a chromosome formula of 2n=2x=6m+2t+4sm and of 2n=2x=8m+2sm+2t, respectively. Eleutherine bulbosa was also found to have a bimodal karyotype. The most recent finding of this study is the discovery of sub-metacentric and telocentric chromosome morphologies, which have never been seen in previous studies.